Pregnant sow behavior when housed in groups and singly - J V Craig (Kansas Agricultural Experiment Station Research Reports, 1982)
Pregnant sow housing varies considerably from area to area in Australia. Thus, group housing amounts to less than 10% in Queensland, but probably exceeds 50% in Victoria. Confinement of pregnant sows in individual stalls is the most common alternative to group housing, but sows on some farms are separated from each other by tethers. When group housing is replaced by individual stalls or tethers, piggery managers often cite "bullying" of subordinate sows by dominant ones, especially during feeding, as a major problem leading to the change. Nevertheless, animal welfare proponents object to physical isolation of pregnant sows. McBride proposes that sows deprived of ability to control recurring aversive events in their environment may suffer from "learned helplessness" and are therefore less able to cope. Close confinement of sows in relatively barren surroundings, Whether in individual or group housing, may increase the risk of "learned helplessness" and associated symptoms of stress.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Behavior; Housing